Physical activity participation, flourishing and academic engagement in adolescents with obesity. - McCoy, Stephanie; Rupp, Kristie (Pediatric Obesity, 2021)
Background: Adolescents with obesity are less likely to flourish and be academically engaged in comparison to their healthy weight peers. However, it is unknown how participation in physical activity influences flourishing and academic engagement in adolescents with obesity. The current study examined engagement in varying levels of physical activity and the likelihood of flourishing and academic engagement in adolescents with obesity. Methods: Analyses included 26 764 adolescents, ages 10–17 years, from the parent-reported, combined 2016–2017 National Survey of Children's Health. Participants were grouped by physical activity levels (none, low, moderate, daily). Outcome variables included flourishing (finishing tasks, staying calm when faced with a challenge and showing interest in new things) and academic engagement (completing all required homework and caring about doing well in school). Logistic regression models, adjusted for age, sex, race, household income, highest level of education in the household, behavioural conduct problems and depression assessed the likelihood of each outcome comparing physical activity levels among adolescents with obesity. Results: Adolescents with obesity who participated in any amount of physical activity (low, moderate and daily) or sports had significantly greater likelihood of flourishing and academic engagement compared those that did not engage in any physical activity (p's ¡ 0.05). Conclusions: Participation in even low amounts of physical activity or participation in sports increases the likelihood of flourishing and academic engagement in adolescents with obesity, which expands on previous findings that adolescents with obesity are less likely to flourish and be academically engaged in comparison to their healthy weight peers. © 2021 World Obesity Federation
Keywords: Adolescent; Child; Exercise; Health Status; Humans; Pediatric Obesity; Schools; adolescence; adolescent; child; childhood obesity; dept.hms; exercise; flourishing; health status; human; obesity; peer-reviewed; physical activity; school